Register in Persaudaraan Setia Hati: Sociolinguistics study - Juwita Dwi Kartikasari; S. Sumani; Rosita Ambarwati (English Teaching Journal : A Journal of English Literature, Language and Education, 2018)
Madiun is a regency in East Java which is known as Kampung Pesilat. Persaudaraan Setia Hati is an organization was made by Ki Ngabehi Surodiwirdjo, Persaudaraan Setia Hati is a way of living and a life’s path. That is not a fighting sport but a fighting art. A fighting sport is a struggle with another and a fighting art is a struggle with oneself. Persaudaraan Setia Hati is a combination of the two brotherhood and founded on five basic principles, brotherhood/ friendship, sport, self-defense, art and culture, and spiritual development which represent in the symbols of the Persaudaraan Setia Hati emblem. Thus, the researcher uses socio-cultural theory which appear register forms. The objectives of this study are to describe the register, context, social meaning of register used by Persaudaraan Setia Hati. The approach of this study is qualitative research and the type of the research is case study because the researcher can identify the register forms that used Persaudaraan Setia Hati and social meaning in society. The researcher shows the data on screenshot of the original conversation each member which is taken from Facebook group Persaudaraan Setia Hati. Analysis technique flow model of this study are data condensation, displaying data, and concluding. The result of this study are (1) there are some register words found in the data that categories the context as follows: the participants are about the relationship between each member, the setting describes from the place where the conversation happened, the topic are about daily life experiences, the function as the motivation and self reminder for each member (2) social meaning are about brotherhood/friendship, sport, self-defense, art and culture, spiritual development.